2013
DOI: 10.4236/mrc.2013.23016
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity and Selectivity of Unsupported Dodecatungstophosphoric Acid, and Its Cesium and Potassium Salts Supported on Silica

Abstract: Potassium and cesium salts of tungstophosphoric acid were prepared by precipitation method. For sake of comparison HPW, potassium and cesium tungstophosphates were supported on silica (20 wt%) by wet impregnation method. The catalysts were characterized by XRD, nitrogen adsorption-desorption measurements at 77 K, and the catalytic activity has been studied by using the catalytic conversion of tert-butanol at temperatures between 323 and 423 K. The results revealed that all of the catalysts were active and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Substitution of one proton of tungstophosphoric acid (HPW) by cesium or potassium cation exerted no measurable effect on the catalytic activity. 11 15 Moreover, Okuhara et al also reported the insoluble heteropoly compounds as highly active catalysts for liquidphase reactions because of the high activity of Cs 2.5 salt. This is due to the large number of surface acid sites and its acid−base bifunctional nature, in which a cesium ion possibly increases the basicity of the heteropolyanion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of one proton of tungstophosphoric acid (HPW) by cesium or potassium cation exerted no measurable effect on the catalytic activity. 11 15 Moreover, Okuhara et al also reported the insoluble heteropoly compounds as highly active catalysts for liquidphase reactions because of the high activity of Cs 2.5 salt. This is due to the large number of surface acid sites and its acid−base bifunctional nature, in which a cesium ion possibly increases the basicity of the heteropolyanion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, solid acid catalysts can also reduce the production cost because they could be easily recycled and used several times without loss of catalytic activity. Substitution of one proton of tungstophosphoric acid (HPW) by cesium or potassium cation exerted no measurable effect on the catalytic activity . Filek et al studied the preparation and characterization and tested the catalytic properties of GaPW 12 O 40 and InPW 12 O 40 for the etherification of ethanol .…”
Section: Introductionmentioning
confidence: 99%
“…The increase in surface area and the proton conductivity of metal-substituted TPA are responsible for achieving high fuel cell performance. 21,22 Although there exist many studies on the use of metal-substituted TPA for catalysis, very few report their use for fuel cell applications. Cs-TPA was used as the conducting filler for PEM fuel cell applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, metal-modified HPA supported on the suitable solid is an efficient method to improve the catalytic performance. Recently, benzylation and oxidation reactions over metal-modified HPAs supported on some solids have been studied, but the benzoylation reaction is still rarely reported.…”
Section: Introductionmentioning
confidence: 99%